Redox state and the sirtuin deacetylases are major factors that regulate the acetylation status of the stress protein NQO1 - Siegel, David; Harris, Peter S.; Michel, Cole R.; de Cabo, Rafael; Fritz, Kristofer S.; Ross, David (Frontiers in Pharmacology, 2022)
The stress induced protein NQO1 can participate in a wide range of biological pathways which are dependent upon the interaction of NQO1 with protein targets. Many of the protein-protein interactions involving NQO1 have been shown to be regulated by the pyridine nucleotide redox balance. NQO1 can modify its conformation in response to changes in the pyridine nucleotide redox balance. Sites on the C-terminal and helix 7 regions of NQO1 have been identified as potential areas that may be involved in redox-dependent protein-protein interactions. Since post-translational modifications of proteins, including lysine acetylation, can modify the functionality of proteins, we examined whether the redox dependent conformational changes induced in NQO1 would alter lysine acetylation. Recombinant NQO1 was incubated with and without NADH then acetylated non-enzymatically by acetic anhydride or S-acetylglutathione (Ac-GSH). NQO1 acetylation was determined by immunoblot and site-specific lysine acetylation was quantified by mass spectrometry (MS). NQO1 was readily acetylated by acetic anhydride and Ac-GSH. Interestingly, despite a large number of lysine residues (9%) in NQO1 only a small subset of lysines were acetylated and the majority of these were located in or near the functional C-terminal or helix 7 regions. Reduction of NQO1 by NADH prior to acetylation resulted in almost complete protection of NQO1 from lysine acetylation as confirmed by immunoblot analysis and MS. Lysines located within the redox-active C-terminus and helix 7 regions were readily acetylated when NQO1 was in an oxidized conformation but were protected from acetylation when NQO1 was in the reduced conformation. To investigate regulatory mechanisms of enzymatic deacetylation, NQO1 was acetylated by Ac-GSH then exposed to purified sirtuins (SIRT 1-3) or histone deacetylase 6 (HDAC6). NQO1 could be deacetylated by all sirtuin isoforms and quantitative MS analysis revealed very robust SIRT2 deacetylation of NQO1, specifically at K262 and K271 in the C-terminal region. No deacetylation of NQO1 by HDAC6 was detected. These data demonstrate that the same subset of key lysine residues in the C-terminal and helix 7 regions of NQO1 undergo redox dependent acetylation and are regulated by sirtuin-mediated deacetylation.